Optimization of the thermal comfort behavior of bed linen using different softening formulations - Soares, Graça M. B. (2012)
This work aims to assess the optimization of the thermal comfort properties of bed linen using different commercial softeners often used in home textiles finishing. Objectively, we intend to study the effect of different softeners and their concentrations, based on non-ionic polyethylene dispersions and a cationic silicone softener micro-emulsion on textile properties. Thermal comfort is related to the sensations of heat or cold, moisture or dryness and influence the performance of textile products used near the skin, such as bed linens. Thus, studies concerning thermal measurements of linen finished samples were carried out using the Alambeta test apparatus. The research shown that thermal related properties are influenced by polyethylene softener Finally, selected softened samples of bed linen were evaluated by a dry thermal manikin to validate the conclusions.